1998
DOI: 10.3177/jnsv.44.561
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Percent Body Fat by the Newly Developed Sulfur Hexafluoride Dilution Method and Air Displacement Plethysmography.

Abstract: SummaryThe reliability and validity of two newly developed den sitometric methods for determining the human body volume and per cent body fat (%FAT), the sulfur hexafluoride dilution method (SHF) and air displacement plethysmography (ADP), were evaluated in com parison with the underwater weighing method (UWW). Seven healthy male volunteers (age 31 to 44, mean height 166.0cm, weight 61.4kg) participated in this study. The same-day test-retest coefficients of variation (CVs) for body volume and %FAT measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
4
12
0
Order By: Relevance
“…CVs for adults ranged from 1.7% -4.5%BF within a single day of testing (Biaggi et al, 1999;Iwaoka et al, 1998;McCrory, et al, 1995;Miyatake, Nomaka, & Fujii, 1999;Sardinha, Lohman, Teixeira, Guedes, & Going, 1998) and from 2.0% -2.5%BF among studies conducted between days (Fields et al, 2002;Levenhagen et al, 1999;Miyatake et al, 1999;Nunez et al, 1999). These CVs are similar to those studies using HD and DXA methodology (e.g., 1.3% -3%; Ellis, 2001;Pierson et al, 1991;van der Ploeg, Crockett, Modra, Withers, & Gunn, 2000).…”
Section: Validity and Reliability Of Adpsupporting
confidence: 73%
See 1 more Smart Citation
“…CVs for adults ranged from 1.7% -4.5%BF within a single day of testing (Biaggi et al, 1999;Iwaoka et al, 1998;McCrory, et al, 1995;Miyatake, Nomaka, & Fujii, 1999;Sardinha, Lohman, Teixeira, Guedes, & Going, 1998) and from 2.0% -2.5%BF among studies conducted between days (Fields et al, 2002;Levenhagen et al, 1999;Miyatake et al, 1999;Nunez et al, 1999). These CVs are similar to those studies using HD and DXA methodology (e.g., 1.3% -3%; Ellis, 2001;Pierson et al, 1991;van der Ploeg, Crockett, Modra, Withers, & Gunn, 2000).…”
Section: Validity and Reliability Of Adpsupporting
confidence: 73%
“…HD continues to be the criterion method of choice for body composition measurement, being compared to DXA , ADP (Claros, Hull, & Fields, 2005;Holmes, Gibson, Cremades, & Mier, 2011), BIA (Biaggi et al, 1999) and sulphur hexafluoride dilution (Iwaoka et al, 1998), however, for the purposes of this review only ADP will be discussed as it is the closest to HD and they both use the twocompartment model. ADP and HD have been used to validate each other in both adults Biaggi et al, 1999) and children (Holmes, et al, 2011;Claros, et al, 2005); however, the adult population will be further discussed.…”
Section: Validity and Reliability Of Hdmentioning
confidence: 99%
“…McCrory et al (1995) observed that within-subject test-to-test reliability was better in the BP (CV ¼ 1.7%) than in HW (CV ¼ 2.3%). Iwaoka et al (1998) reported comparable results (CV for BP ¼ 3.7%, CV for HW ¼ 4.3%) following a similar protocol. Intradevice reliability of the BP is similar to that reported for DXA (Jensen et al, 1993).…”
Section: Introductionsupporting
confidence: 65%
“…The agreement in %BF estimates between the two BP units, in terms of mean difference (0.571.2 %BF), 95% limits of agreements (À1.9-2.9 %BF) and within-subject CV (3.172.2%), was found to be better than that observed by Collins et al (2004), and was similar to that calculated using measured TGV in this study. Previous studies have reported that intradevice reliability, as indicated by within-subject CV for repeated %BF measurements by a single BP, ranged from 1.7 to 3.7% within a day (McCrory et al, 1995;Iwaoka et al, 1998), and from 2.0 to 2.3% between days (Levenhagen et al, 1999;Miyatake et al, 1999) for adults. A comparison of these CVs with those obtained from the current study indicates that the BP has a similar intra and interdevice reliability for assessing %BF.…”
Section: Discussionmentioning
confidence: 99%
“…McCrory et al, 5 Nuñez et al 11 and Elia & Ward 17 found no over-or underestimation. Collins et al, 7 and Iwaoka et al, 8 found that ADP underestimated %BF -more so in leaner individuals than in those with more fat. It should be noted that all of the subjects in the Collins et al and Iwaoka et al studies were males.…”
Section: Discussionmentioning
confidence: 99%